Penerapan Metode Behaviorally Anchor Rating Scale Pada Sistem Informasi E-Kinerja Pegawai - Sukma, Cahyaning Arum; Purwanto, Eko; Permatasari, Hanifah (Politeknik Indonusa Surakarta, 2022)
Polanharjo is one of the sub-districts in Klaten district, Central Java province. Employee performance appraisal in Polanharjo sub-district is still done manually, namely by collecting files directly and the results are written manually in available documents. This study uses direct observation method to obtain data regarding employee performance appraisal in Polanharjo District. The system development method used in this research is the prototype method. Implementation of the system using the PHP programming language and MySQL database. The method of evaluating employee performance in this study uses the behaviorally anchor rating scale method. Testing the information system for evaluating employee performance through black box testing, while testing users by distributing questionnaires and obtaining a value of 82.2% with the conclusion that the system can be accepted by employees.